Masked malnutrition - Sanjay Kalra; Sourabh Sharma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
This brief communication highlights the importance ofmalnutrition in primary practice. Malnutrition may bemasked, or may not be obvious (hidden hunger, i.e.,micronutrient deficiency, sarcopenic obesity,lipokathexis). At the same time, malnutrition itself maymask or delay the diagnosis and treatment of otherdiseases. Even in today’s world, the primary carephysicians must remain alert for symptoms and signs ofmacro-and micro-malnutrition. Keywords: Carbohydrates, fats, lipids, macronutrients,malnutrition, micronutrients, minerals, nutrition, protein,vitamins